Scrum, Kanban or a Mix of Both? A Systematic Literature Review - Ozkan, Necmettin; Bal, Sevval; Erdogan, Tugba Gurgen; Gok, Mehmet Sahin (2022 17th Conference on Computer Science and Intelligence Systems (FedCSIS), 2022)
Among the Agile methods, Scrum and Kanban are widely used in software development and they are considered the two most effective ones influencing the direct results of projects. Despite the importance of knowing their relative strengths and advantages and integrating them to achieve better results than individual use, none of the secondary studies provide extensive knowledge on the topic. In this paper, we performed a Systematic Literature Review (SLR) study to investigate the characteristics of the empirical studies which involve Scrum and Kanban by comparing or integrating them. Our final set includes 38 studies posing primary information on the advantages of each method over another one, the properties including artifacts, roles, and events from Scrum and Kanban in combining them in a hybrid way, and the properties of transitions from one to another such as transition directions (Scrum to Kanban, Kanban to Scrum or Scrum/Kanban to Hybrid), transition years, and transition reasons. The outputs can be interesting for both industry and researchers. For example, nearly all of the transitioning organizations are moving from Scrum to Kanban or to hybrid method. Among the reasons for the transitions, the problems experienced with Scrum are remarkable. In comparison, Kanban stands out clearly in a positive way. Almost all of the teams combining both use flow instead of a sprint.